The Ability of Gracilaria Sp. to Absorb Ammoniac (NH3-N) and its Effect on Chlorophyll Content and Growth - Yudi Nurul Ihsan; Rizky K. Bangsa; Kalysta Fellatami; Tri Dewi K. Pribadi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
One of the most commonly found component of domestic waste in coastal areas is ammoniac. Phytoremediation techniques can be done to reduce ammoniac concentrations. In this research, the technique uses the macroalgae Gracillaria sp. This study aims to measure the optimum ability of Gracillaria sp. to absorb ammoniac and its effect towards the primary productivity of water exposed to ammoniac. The research was done by comparing the reduction of ammoniac in seawater, which is used as a medium of experiment for 120 hours, with the ammoniac concentration in Gracillaria sp. The research method used was an experimental method with a completely randomized design of four treatments and three repetitions. The effectiveness results of ammoniac reduction by macroalgae in treatment A, B, C and D are 41.21%, 50.27%, 47.37% and 43.05% respectively. The initial concentration results of ammoniac in Gracillaria sp. was 20.75 mg/kg and the final concentrations in treatment A, B, C and D were 21.08 mg/kg, 21.20 mg/kg, 22.87 mg/kg and 24.44 mg/kg respectively. The measurement results of chlorophyll-a concentration in water coloumn ranged between 0.015 - 0.027 mg/l.